(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
In Central Iran Eocene copper deposit occurs in volcanic arc setting hosted by Oligocene porphyrytic granite, which is intruded by a series of Miocene quartz-monozodiorite to granodiorite rocks. The intrusions were intruded into late cretaceous and Eocene sedimentary volcano-clastic and volcanic rocks. Major and accessory minerals with petrography data suggest that all copper bearing intrusions are I-type volcanic granitoids. Four hydrothermal alteration zones have been recognized in the porphyritic intrusions and surrounding rocks. This study identified the Cu-Mo mineralization at Ali-Abad area as a typical porphyritic Cu-Mo deposit, formed in an arc-related environment during Mid-Cenozoic era.